Ambitious framework nation: Germany in NATO. Bundeswehr capability planning and the "Framework Nations Concept" - Rainer Glatz; Martin Zapfe (Stiftung Wissenschaft und Politik (SWP), 2017)
Berlin is pursuing ambitious plans for security and defence, with significant potential for the Bundeswehr and European partner militaries. In the long-term, the Bundeswehr could well become Europe's indispensable army, with Germany as a 'framework nation' contributing decisively to NATO's readiness. This will require the future German gov-ernment to accept an unaccustomed politico-military leadership role. It will also be necessary to increase defence spending for the long term.
Keywords: 320